HERO (Health Economics in Radiation Oncology): A Pan-European Project on Radiotherapy Resources and Needs. Issue 2 (February 2015) - Lievens, Y.; Dunscombe, P.; Defourny, N.; Gasparotto, C.; Borras, J.M.; Grau, C.
Abstract Radiotherapy continues to evolve at a rapid rate in technology and techniques, with both driving up costs in an era in which health care budgets are of increasing concern at every governmental level. Against this background, it is clear that the radiotherapy community needs to quantify the costs of state of the art practice and then to justify those costs through rigorous cost-effectiveness analyses. The European Society for Radiotherapy and Oncology-Health Economics in Radiation Oncology project is directed towards tackling this issue in the European context. The first step has been to provide a validated picture of the European radiotherapy landscape in terms of the availability of equipment, personnel and guidelines. An 84-item questionnaire was distributed to the 40 countries of the European Cancer Observatory, of which 34 provided partial or complete responses. There was a huge variation in the availability and sophistication of treatment equipment and staffing levels across Europe. The median number of MV units per million inhabitants was 5.3, but there was a seven-fold variation across the European countries. Likewise, although average staffing figures per million inhabitants were 12.8 for radiation oncologists, 7.6 for physicists, 3.5 for dosimetrists, 26.6 for radiation therapists and 14.8 for nurses, there was a 20-fold variation, even after grouping personnel with comparable duties in the radiotherapy process. Guidelines for capital and human resources were declared for most countries, but without explicitly providing metrics for developing capital and human resource inventories in many cases. Although courses delivered annually per resource item – be it equipment or staff – increase with decreasing gross national income (GNI) per capita, differences were observed in equipment and staff availability in countries with a higher GNI/n, indicating that health policy has a significant effect on the provision of services. Although more needs to be done to increase access to radiotherapy in Europe, the situation has improved considerably since the comparable RadioTherapy for Cancer: QUAnification of Infrastructure and Staffing Needs (QUARTS) study reported in 2005.